2007
DOI: 10.1021/la7007045
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Biofunctionalization of Silicon Nitride Surfaces

Abstract: Covalently attached organic monolayers on etched silicon nitride (SixN4; x >/= 3) surfaces were prepared by reaction of SixN4-coated wafers with neat or solutions of 1-alkenes and 1-alkynes in refluxing mesitylene. The surface modification was monitored by measurement of the static water contact angle, XPS, IRRAS, AFM, and ToF-SIMS, and evidence for the formation of Si-C bonds is presented. The etching can be achieved by dilute HF solutions and yields both Si-H and N-H moieties. The resulting etched SixN4 surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 63 publications
3
94
0
3
Order By: Relevance
“…Arafat et al [25] concluded that fragments corresponding to Si-C bonds in their SIMS spectra were indicative of covalent binding between the monolayer of alkyl chains and the silicon nitride substrate, as the low ion flux used in TOF-SIMS makes recombination above the surface an unfavorable process. Additionally, neutral ions may be ejected from the surface and, due to the internal kinetic energy, subsequently dissociate to form the detected ion.…”
Section: Resultsmentioning
confidence: 99%
“…Arafat et al [25] concluded that fragments corresponding to Si-C bonds in their SIMS spectra were indicative of covalent binding between the monolayer of alkyl chains and the silicon nitride substrate, as the low ion flux used in TOF-SIMS makes recombination above the surface an unfavorable process. Additionally, neutral ions may be ejected from the surface and, due to the internal kinetic energy, subsequently dissociate to form the detected ion.…”
Section: Resultsmentioning
confidence: 99%
“…Alkene-based monolayers were also formed on flat Si x N 4 [Arafat, et al, 2007& Arafat, et al, 2004, (Fig. 6) and 6H-SiC and polycrystalline 3C-SiC [Rosso, et al, 2008b] using thermal conditions close to those used for the surface modification of silicon.…”
Section: Organic Monolayers On the Surfaces Of Silicon-rich Materialsmentioning
confidence: 98%
“…Semi-carbazides and esters can be easily converted to amine [Coffinier, et al, 2007] and acid groups [Rosso, et al, 2009], respectively, which can serve for further attachment of biomolecules or biorepelling molecules and polymers [Asanuma, et al, 2006& Coffinier, et al, 2005& Love, et al, 2005a. The advantage of alkene-based monolayers is their stability, mainly due to the absence of a silicon oxide layer, and the presence of stable and non-polar Si-C bonds, in the case of Si [Linford & Chidsey, 1993] and Si x N 4 , [Arafat, et al, 2007] [Rosso, et al, 2008b] and stable C-O-C bonds in the case of SiC surfaces [Rosso, et al, 2008a]. Stability measurements revealed the outstanding stability of thermally produced 1-hexadecene monolayers on Si x N 4 substrates, in acidic or basic conditions at 60 ºC, with changes in contact angles of less than 5º after 4 h of such a treatment [Arafat, et al, 2007].…”
Section: Organic Monolayers On the Surfaces Of Silicon-rich Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Devices and applications exploiting these beneficial native features can be augmented and improved using designer metal overlayers that fulfill structural roles, serve as electrodes, and provide alternative surface chemistry options, including as a platform for subsequent thiol monolayer self-assembly. The field of nanopore single-molecule sensing offers compelling examples of the prospects of merging SiNx thin films and designer metal layers into devices, and does this within a nanofluidic context where the need for versatile metallizing approaches is clear.…”
mentioning
confidence: 99%